Amino DSA analogues as payloads for antibody-drug conjugates with multiple sites for conjugation. Initial studies and solid phase synthesis. (25th May 2021) - Cominetti, Marco M.M.D.; Goddard, Zoë R.; Howman, Chloe E.; O'Connell, Maria A.; Searcey, Mark
Graphical abstract: Highlights: Amino-Duocarmycin analogues have potential as antibody drug conjugate payloads. An amino-duocarmycin subunit suitable for solid phase methods was synthesised. Solid phase synthesis was used successfully to make an amino-duocarmycin analogue. Abstract: Duocarmycins are highly potent and promising anticancer payloads for ADC applications. They tolerate a range of chemical modifications which allow the chemist to modulate both their biophysical and pharmacological properties. The possibility to synthesize these payloads on resin and orthogonally add linkers while immobilized on the solid phase, would allow a combinatorial design of payload analogues with linkers, potentially aided by automation. Working towards this goal, we report a concise and high yielding synthesis of an alkylating unit suitable for solid phase synthesis (10, 9 steps, 34% yield) and demonstrate its applicability to the synthesis of duocarmycin SA analogues (19, 20 ). An intermediate for traditional solution phase synthesis (8 ) is also described in 7 steps and 44% yield. A side reaction with potential application to the stereoselective synthesis of these derivatives has also been described.